Receptor Mechanisms Mediating the Pro-Nociceptive Action of Hydrogen Sulfide in Rat Trigeminal Neurons and Meningeal Afferents - Koroleva, Kseniya; Mustafina, Alsu; Yakovlev, Aleksey; Hermann, Anton; Giniatullin, Rashid; Sitdikova, Guzel (Frontiers in Cellular Neuroscience, 2017)
Hydrogen sulfide (H2S), a well-established member of the gasotransmitter family, is involved in a variety of physiological functions, including pro-nociceptive action in the sensory system. Although several reports have shown that H2S activates sensory neurons, the molecular targets of H2S action the trigeminal nociception, implicated in migraine, remains controversial. In this study, using suction electrode recordings, we investigate the effect of the H2S donor, sodium hydrosulfide (NaHS), on nociceptive firing in rat meningeal trigeminal nerve fibers. The effect of NaHS was also explored with patch-clamp and calcium imaging techniques on isolated trigeminal neurons. NaHS dramatically increased the nociceptive firing in trigeminal nerve fibers. This effect was abolished by the TRPV1 inhibitor capsazepine but was partially prevented by the TRPA1 blocker HC 030031. In a fraction of isolated trigeminal neurons, NaHS transiently increased the amplitude of capsaicin-induced currents. Moreover, NaHS by itself induced inward currents in sensory neurons, which were abolished by the TRPV1 inhibitor capsazepine suggesting involvement of TRPV1 receptors. In contrast, the inhibitor of TRPA1 receptors HC 030031 did not prevent the NaHS-induced currents. Imaging of large population of trigeminal neurons revealed that NaHS induced calcium transients in 41 % of tested neurons. Interestingly, this effect of NaHS in some neurons was inhibited by the TRPV1 antagonist capsazepine whereas in others it was sensitive to the TRPA1 blocker HC 030031. Our data suggest that both TRPV1 and TRPA1 receptors play a role in the pro-nociceptive action of NaHS in peripheral trigeminal nerve endings in meninges and in somas of trigeminal neurons. We propose that activation of TRPV1 and TRPA1 receptors by H2S during neuro-inflammation conditions contributes to the nociceptive firing in primary afferents underlying migraine pain.